The use of the Newcastle Control Score in the management of intermittent exotropia. Issue 2 (4th October 2006) - Buck, Deborah; Hatt, Sarah R; Haggerty, Helen; Hrisos, Susan; Strong, Nicholas P; Steen, Nicholas I; Clarke, Michael P
Abstract : Aim: To evaluate the use of the Newcastle Control Score (NCS) in the management of intermittent exotropia (X(T)). Participants and methods: Children aged <11 years with X(T) had an assessment of NCS as part of routine management. Other data collected included visual acuity, near and distance alignment with alternating prism cover test and near (Frisby test) and distance stereoacuity (Frisby Davis Distance Stereotest (FD2TM)). Analysis involved correlation between baseline NCS, angle and stereoacuity, examination of change over time and logistic regression to determine predictors of surgery. Results: Baseline data were obtained on 272 children and follow-up data on 157. Mean (SD) age was 4 (1.9) years. Complete NCSs were obtained for all except one child at baseline, and all children at follow-up. At baseline, total NCS and the home control component were correlated with near stereo (r = –0.22, p<0.01 and r = –0.19, p<0.02, respectively), near alignment (r = 0.34, p<0.001 and r = 0.19, p<0.02) and distance alignment (r = 0.30, p<0.001 and r = 0.26, p<0.001). The clinic near control component was correlated with near alignment (r = 0.39, p<0.001), but not near stereoacuity, and the clinic distance control with near alignment (r = 0.16, p<0.02), distance alignment (r = 0.27, p<0.001) and distance stereoacuity (r = –0.25, p<0.03). A high (poor) NCS (⩾4) at the latest follow-up predicted surgery (p<0.001, OR 29.3, 95% CI 6.2 to 138.7). Conclusion: The NCS is a useful measure of the clinical severity of X(T), can be used to serially assess improvement or deterioration and is a useful tool for the management of these patients.